2018
DOI: 10.3889/oamjms.2018.282
|View full text |Cite
|
Sign up to set email alerts
|

Renal Arteries Embolization in Unresectable Clear Cell Renal Carcinoma: First Time Experience at Haji Adam Malik Hospital

Abstract: OBJECTIVE:To report a case of renal arterial embolisation (RAE) in unresectable renal tumour before nephrectomy.CASE REPORT:On presentation, the clinical features of this patient, including medical history, signs and symptoms, imaging examinations were recorded. After diagnosis and initial treatment, the result and histopathological examination were performed and discussed. We performed RAE in the unresectable renal tumour in the 28-year-old male that was complaining a palpable pain right flank mass and interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
1
0
1
Order By: Relevance
“…J H Park et al reported [38] that for patients with inoperable RCC, TAE using lipiodol + ethanol emulsion was an effective and safe treatment. Noor Riza Perdana et al reported [39] that RAE is an effective treatment for large unresectable renal tumors and can reduce mortality. T Kato et al reported [40] that chemoembolization with mitomycin C microcapsules is a very effective treatment for renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…J H Park et al reported [38] that for patients with inoperable RCC, TAE using lipiodol + ethanol emulsion was an effective and safe treatment. Noor Riza Perdana et al reported [39] that RAE is an effective treatment for large unresectable renal tumors and can reduce mortality. T Kato et al reported [40] that chemoembolization with mitomycin C microcapsules is a very effective treatment for renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…В литературе представлен не совсем однозначный опыт применения эмболизации почечной артерии перед нефрэктомией при больших опухолях, сопровождающихся развитием массивной патологической сосудистой сети [1,2]. Это способствовало снижению объема кровопотери, однако некоторые авторы испытывали существенные технические трудности при выделении и лигировании артерии, а также с выраженным болевым синдромом и гипертермией в течение до 48 ч после процедуры [2].…”
unclassified